Safra kesesi kanseri: İki olgu - (:unkn) unknown (My University, 2000)
Safra kesesi kanseri, erken evrede kolesistektomi ile kür sağlanabilen, ileri evrelerde ise radikal cerrahi girişimlerle dahi tatmin edici sağkalım oranları elde edilemeyen, safra kesesinin nadir görülen bir hastalığıdır. Erken tanı ve kanserin yayılım düzeyi prognozu belirler. Bu yazıda, safra kesesi polibi ön tanısıyla iki yıl izlendikten sonra kanser nedeniyle ameliyat edilen, adjuvan kemoterapi ve kemoembolizasyona rağmen 10. ayda kaybedilen 65 yaşında bir kadın hasta ile kolesistolitiyazis tanısıyla yapılan laparoskopik kolesistektomi sonrası rastlantısal olarak safra kesesi kanseri saptanarak izlenen 44 yaşında bir kadın hasta sunuldu.

Cancer of the gallbladder is an uncommon disorder that can be cured with cholecystectomy in the early stage, whereas its prognosis is poor in advanced stages even with radical surgical approaches. We report two female patients, aged 65 and 44 years, respectively. The former was followed-up for two years with a diagnosis of gallbladder polyp, after which gallbladder cancer was documented and treated by cholecystectomy. She died in the 10th postoperative month despite adjuvant chemotherapy and chemoembolization. In the latter, an incidental cancer was diagnosed histopathologically following laparoscopic cholecystectomy for cholecystolithiasis.
Carcinoma of the gallbladder: Report of two cases
Keywords: Gastroenteroloji ve Hepatoloji; Tıbbi Araştırmalar Deneysel; Onkoloji; Cerrahi